Sensitivity caused by Dermatophagoides pteronyssinus and D. farinae (Astigmata: Pyroglyphidae) in subjects with allergic rhinitis - Dhaliwal, Amandeep Kaur; Kaur Chahal, Manpreet (Systematic and applied acarology, 2022)
The house dust mites (HDMs), defined here as members of the family Pyroglyphidae, are present just about everywhere in human dwellings and act as an important risk factor for allergic rhinitis (AR). They are a major perennial allergen source that causes AR. In the present study, 160 subjects clinically diagnosed with AR from the Department of Ear Nose Throat (ENT), Government Rajindra Medical College and Hospital, Patiala, India, and 30 non-allergic healthy, control individuals were selected. Blood samples were taken from all these study subjects for serological testing and ImmunoCAP™ Phadia™ 100 was used for the detection of total and HDM specific immunoglobulin E (IgE) levels. To detect total IgE levels, a mixture of 14 different allergens was used and, for HDM specific IgE, a mixture of Dermatophagoides pteronyssinus (Trouessart) and D. farinae Hughes allergens. Dust samples were taken from mattresses used by the study subjects with the help of a vacuum cleaner. A floatation method was used for the extraction of mites. Hoyer’s medium was used for the preparation of slides for microscopy. Total IgE levels were elevated in all AR subjects and HDM specific IgE levels were found to be positive in 54.38% of them. Analysis of dust samples showed that 72.50% of samples from the mattresses of AR subjects were found to be positive for the HDMs D. pteronyssinus and D. farinae and 33.33% of those from the control group. Total and HDM specific IgE levels of AR subjects showed statistically significant correlation with each other, but in the control group no such correlation was found. Moreover, a significant result was found between the positive HDM specific IgE levels and the number of D. pteronyssinus and D. farinae found in their respective dust samples. In conclusion, the total IgE and positive HDM specific IgE levels showed that there was a chance of allergic reaction in rhinitis subjects. Furthermore, the significant statistical analysis between positive HDM specific IgE levels against D. pteronyssinus and D. farinae, and the higher prevalence of these two species in the houses sampled provided support for these mites being the major allergen sources for the symptoms of AR in the study area.